Kinship Relations and Geographic Constraints in the Social Integration of Meratus Muslim Converts: A Case Study from Patikalain, Indonesia - Ansari, M. Sandri; Hilmy, Masdar; Erawati, Desi (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Religious conversion in remote indigenous communities involves both changes in religious affiliation and the reorganization of social relationships and access to religious resources. Previous studies of Meratus Muslim converts have examined religious guidance, economic empowerment, and cultural adaptation, but the interaction between kinship relations and geographically constrained institutional access remains less clearly understood. This qualitative single-case study examines how these conditions shaped the social integration experiences of Muslim converts in Patikalain, South Kalimantan, Indonesia. Data were collected between February and March 2026 through semi-structured interviews with two converts, a customary leader, and an Islamic preacher, supplemented by four field visits and a review of the 2024 local profile. The data were analyzed through iterative coding, categorization, data display, and theoretically informed interpretation. The two converts described different kinship-mediated pathways to Islam: gradual parental socialization and social validation through observing relatives and community members. The customary leader reported no open conflict over conversion, while field observations and the preacher’s account indicated that difficult access, long distances, and limited communication constrained the regularity of formal religious guidance. The findings identify kinship relations as an immediate source of social connection and geographic conditions as a constraint on institutional religious access. These patterns are context-specific and support the need for regular, culturally responsive guidance rather than a standardized model of intervention.